Establishing the patterns in the formation of oxide films on the alloy Ti6Al4V in carbonic acid solutions - Ivashchenko, Maryna; Smirnova, Olha; Kyselova, Svitlana; Avina, Svetlana; Sincheskul, Alexander; Pilipenko, Alexei (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports results of studying the features of the formation of thin interference-colored oxide films on the alloy Ti6Al4V alloy in solutions of carboxylic acids. It has been established that a change in voltage on the cell corresponding to the molding dependence of the alloy depends on the anodic current density. At current densities <0.5 A∙dm–2, a continuous oxide film is not formed at the alloy surface and the assigned voltage value is not reached. An increase in current density to values higher than 0.5 A∙dm–2 predetermines a linear change in voltage over time with followed by reaching the assigned magnitude U. The maximum film thickness for these conditions is defined by the voltage magnitude and does not depend on the electrolysis mode. Color of the oxide film is defined by the specified value for the molding voltage and does not depend on current density, nature and concentration of carboxylic acid. A match between the molding dependences of oxidation obtained in different electrolytes suggests that the formation of oxide proceeds in line with the same mechanism. The obtained data are explained by the fact that the formation of oxide under the galvanic static mode takes place under conditions of the presence of a constant potential gradient in the oxide film. An increase in the voltage magnitude applied to the cell predetermines a proportional increase in the maximum oxide thickness, since it leads to an increase in the amount of electricity passed through the cell and a corresponding increase in the mass of the oxidized metal. Results of the study into determining the effect of the nature of carboxylic acid on the formation process of an oxide film on the alloy Ti6Al4V using the method of electrochemical oxidation have demonstrated that the nature of the electrolyte does not affect the characteristics of its formation. The obtained data allow us to suggest that the choice of an electrolyte for the development of a technology for electrochemical oxidation of titanium implants should be based on the results of studying the functional properties of the obtained coatings